Flagella and Their Properties Affect the Transport and Deposition Behaviors of Escherichia coli in Quartz Sand - Mengya Zhang; He, Lei; Jin, Xin; Fan Bai; Meiping Tong; Ni, Jinren (Environmental Science and Technology, 2021)
The effects of flagella and their properties on bacterial transport and deposition behaviors were examined by using four types of Escherichia coli (E. coli) with or without flagella, as well as with normal or sticky flagella. Packed column, quartz crystal microbalance with dissipation, visible parallel-plate flow chamber system, and visible flow chamber packed with porous media system were employed to investigate the deposition mechanisms of bacteria with different properties of flagella. We found that the presence of flagella favored E. coli deposition onto quartz sand/silica surfaces. Moreover, by changing the porous media porosity and directly observing the bacterial deposition process, local sites with high roughness, narrow flow channels, and grain-to-grain contacts were found to be the major sites for bacterial deposition. Particularly, flagella could help bacteria swim near and then deposit at these sites. In addition, we found that due to the stronger adhesive forces, sticky flagella could further enhance bacterial deposition onto quartz sand/silica surfaces. Elution experiments indicated that flagella could help bacteria attach onto sand surfaces more irreversibly. Clearly, flagella and their properties would have obvious impacts on the transport/deposition behaviors of bacteria in porous media. © 2021 American Chemical Society.
Keywords: Adhesives; article; Bacteria (microorganisms); Bacterial deposition; bacterial flagellum; Bacterial transport; cells; coliform bacterium; contact angle; controlled study; Deposition; Deposition mechanism; elution; Elution experiments; Escherichia coli; Escherichia coli (E. coli); Flagella; flagellum; Grain-to grain contact; hydrophilicity; Ionic strength; nonhuman; Parallel flow; Parallel plate flow chamber; pollutant transport; porosity; Porous materials; Quartz; quartz crystal microbalance; Quartz crystal microbalance with dissipation; Sand; silicate; silicon dioxide; steady state; transport kinetics; zeta potential